1987
DOI: 10.1177/35.1.2878950
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous distribution of glutamine synthetase during rat liver development.

Abstract: Two days before birth, immunohistochemical detection of glutamine synthetase already reveals a heterogeneous distribution pattern related to the vascular architecture of the liver. Only a small number of hepatocytes in the vicinity of the efferent venules show relatively high staining intensity. Before that age, only megakaryocytes show intense staining, while liver parenchyma is only faintly stained. The developmental profile of glutamine synthetase activity shows two periods of increasing enzyme activity: on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
47
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(57 citation statements)
references
References 17 publications
9
47
1
Order By: Relevance
“…GS mRNA, as well as ALB mRNA, was detected in 9 of 10 samples from different donors, CK-18 mRNA was detected in 4 of 10 samples, and AFP mRNA was seen in 2 of 10 samples. GS is known to be expressed in mature hepatocytes [19,20], CK-18 is expressed in the hepatocyte lineage [21,22], and AFP is expressed in hepatic progenitor cells, including oval cells [23,24]. These previous reports support our findings that the cultured cells had the same characteristics as the hepatocyte lineage.…”
Section: Expression Profiles Of Hepatocyte Lineage Markerssupporting
confidence: 89%
“…GS mRNA, as well as ALB mRNA, was detected in 9 of 10 samples from different donors, CK-18 mRNA was detected in 4 of 10 samples, and AFP mRNA was seen in 2 of 10 samples. GS is known to be expressed in mature hepatocytes [19,20], CK-18 is expressed in the hepatocyte lineage [21,22], and AFP is expressed in hepatic progenitor cells, including oval cells [23,24]. These previous reports support our findings that the cultured cells had the same characteristics as the hepatocyte lineage.…”
Section: Expression Profiles Of Hepatocyte Lineage Markerssupporting
confidence: 89%
“…Double labeling with antibodies to glutamine synthetase (Fig. 7B), which is a marker for perivenous hepatocytes (58), showed that GAT2 was expressed at the highest levels in periportal hepatocytes. (The antibody used here to label glutamine synthetase also labeled endothelial cells.)…”
Section: E G I and K)mentioning
confidence: 99%
“…In addition, the localization of GS is distinct from that of other hepatic enzymes by its apparent inflexibility preventing an adaptive shift or an enlargement of the enzyme-positive zone under a variety Of physiological as well as experimental conditions [3,6,10]. Thus, GS serves as a marker for a specialized hepatocyte population [11,12] arising before birth [4] and characterized further by a distinct growth potential in vitro Correspondence address: R. Gebhardt, Physiologischchemisches Institut, Universit~.t Ttibingen, Hoppe-Seyler-Str. 4, D-7400 Tiibingen, FRG [13,14] and presumably by a separate cellular lineage during hepatocarcinogenesis [15].…”
Section: Introductionmentioning
confidence: 99%